Sosialisasi Pemanfaatan Lahan Kosong Untuk Tanaman Cepat Panen Guna Mendukung Ketahanan Pangan Masyarakat Taman Raya Rajeg Tangerang - Riyanto, Riyanto; Basuki, Sucipto; Winanti, Winanti; Nurasiah, Nurasiah; Himmy’azz, Istajib Kulla; Chidir, Gusli; Agistiawati, Eva; Kamar, Karnawi; Maesaroh, Siti; Sukriyah, Sukriyah; Suroso, Suroso; Hulu, Paulinus; Hutagalung, Dhaniel; Fernando, Erick (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
Public awareness of utilizing the narrow land in the Taman Raya Rajeg housing complex is still relatively low. Not all people understand the use of land for food crops. The activity was carried out one day and was attended by 54 participants, the majority of whom were housewives. Education on understanding food security for the community starting from the household is the focus of education this time. The resource person also talked about food security by planting fast-harvesting crops. Community interaction was very good from PKM activities and discussions went well. The activity ended with the handover of 84 fast-harvesting plants such as chilies, tomatoes and eggplants to activity participants and symbolic tree planting.